Fluxos de ações e processos decisórios na gestão pública local: estudos de casos de projetos e programas inovadores em municípios de pequeno porte populacional - Iizuka, Edson Sadao (2008)
The starting point for this study was the contrast between the likely centrality of the decision, held in much of the administrative literature, and the successful experience of digital inclusion implanted in the small town of Piraí-RJ. The originality of this program and its seemingly chaotic way for referral were concerns that propelled the return of the researcher to theories about the decision-making process and the formulation and implementation of public policies. This research focus on the contribution to the debate about the decision and the decision making process from the two questions of the research: what is the centrality of decision making processes for the results achieved in the experiments considered innovative in municipalities of small population (below 30 thousand inhabitants)? And how is it possible to characterize these processes in relation to the academic literature about the subject? The focus of this work is the public area in which the subject of the decision has strong intersection with the theme of the formulation and implementation of public policies. The analysis of the flows of innovative actions in the actions that occurred in municipalities of small population was chosen since it corresponds to more than 80% of all municipalities in Brazil. The limitations of the research are related to the searched area, the type of municipality selected and the projects and programs analyzed. The theoretical references used in this work are as follows: Rational Choice, Limited Rationality, Agenda for Public Policy, Incrementalism, Garbage Can, Sensemaking and, finally, Groping Along. For the linking purpose between these theories and case studies, it was used the logic of each theory and its relation to the process of the experiences reported by the selected participants. The study was conducted in three phases. At first, after the initial issues that emerged from the experience of digital inclusion in Piraí, a bibliographic review of the literature on the decision-making process was made. From this study, an analysis of documents and reports made by managers and technicians from 34 different innovative experiences which were awarded by the Programa Gestão Pública e Cidadania, between 1996 and 2005, which sought to capture the flow of actions that permeated the projects and programs. In the third part, it was taken an in-depth research in four case studies in the states of Bahia, Rio de Janeiro and Sao Paulo, using techniques of oral history and analysis of documents. The cases studied were: Creche Noturna in Laranjal Paulista-SP, Desenvolvimento Local and Inclusão Digital in Piraí-RJ, Desenvolvimento Local Agroambiental in Almadina-BA and finally Manejo da Samambaia Silvestre in Ilha Comprida-SP. The results contrast with the academic literature which logic is predominantly linear and argues that the centrality and importance of the decision in order to get maximum results, and suggest that the propositions of less linear decision making processes and the processes of formulation of public policies that seek to capture the everyday practice of managers – including daily diselegances and imperfections - that best contribute to your understanding.